2011
DOI: 10.1097/scs.0b013e31822e89e3
|View full text |Cite
|
Sign up to set email alerts
|

Ewing Sarcoma of the Jaws

Abstract: Three cases of Ewing sarcoma in the jaw bones are presented. The first patient is a 43-year-old woman with a rapidly growing tumor in the hard palate. The second patient is a 9-year-old girl with tumor in the left mandibular ramus and body. In both patients, the tumors were excised with significant safe margins. However, postoperative histopathologic evaluation revealed the presence of tumor cells in bony margins, necessitating a second surgery. The third patient is a 9-year-old boy with tumor in the right man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The mandible was the most frequent location of the tumor in both our study limited to the oral cavity and in studies involving the head and neck - representing over two-thirds of all the lesions (68%). Our observation coincides with that of Gupta et al ( 10 ), who in a series of 65 cases of primary sarcoma of the jaws recorded a mandibular location in 70.7% of the cases, with a predilection for the ascending ramus ( 28 , 29 ). It has been suggested that the larger amount of bone marrow present in the ascending ramus would account for the greater prevalence of these tumors in that location ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…The mandible was the most frequent location of the tumor in both our study limited to the oral cavity and in studies involving the head and neck - representing over two-thirds of all the lesions (68%). Our observation coincides with that of Gupta et al ( 10 ), who in a series of 65 cases of primary sarcoma of the jaws recorded a mandibular location in 70.7% of the cases, with a predilection for the ascending ramus ( 28 , 29 ). It has been suggested that the larger amount of bone marrow present in the ascending ramus would account for the greater prevalence of these tumors in that location ( 30 ).…”
Section: Discussionsupporting
confidence: 93%